Advanced Strategies for Food-Grade Protein Production: A New E. coli/Lactic Acid Bacteria Shuttle Vector for Improved Cloning and Food-Grade Expression - Tagliavia, Marcello (Microorganisms, 2019)
Food-grade production of recombinant proteins in Gram-positive bacteria, especially in LAB (i.e., Lactococcus, Lactobacillus, and Streptococcus), is of great interest in the areas of recombinant enzyme production, industrial food fermentation, gene and metabolic engineering, as well as antigen delivery for oral vaccination. Food-grade expression relies on hosts generally considered as safe organisms and on clone selection not dependent on antibiotic markers, which limit the overall DNA manipulation workflow, as it can be carried out only in the expression host and not in E. coli. Moreover, many commercial expression vectors lack useful elements for protein purification. We constructed a “shuttle” vector containing a removable selective marker, which allows feasible cloning steps in E. coli and subsequent protein expression in LAB. In fact, the cassette can be easily excised from the selected recombinant plasmid, and the resulting marker-free vector transformed into the final LAB host. Further useful elements, as improved MCS, 6xHis-Tag, and thrombin cleavage site sequences were introduced. The resulting vector allows easy cloning in E. coli, can be quickly converted in a food-grade expression vector and harbors additional elements for improved recombinant protein purification. Overall, such features make the new vector an improved tool for food-grade expression.